OPTIMALISASI PENILAIAN MANDIRI SATUAN PENDIDIKAN AMAN BENCANA (SPAB) DALAM MENDORONG KESIAPAN MENGHADAPI BENCANA GEMPA BUMI DI KAWASAN SESAR OPAK KABUPATEN BANTUL - Inggit Fandayati; Purbudi Wahyuni; Arif Rianto Budi Nugroho; Eko Teguh Paripurno; Johan Danu Prasetya; Kurniawan, Ficky Adi (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
The implementations of self-assessment using Inarisk SPAB's (Disaster Safe School) e-monev tools in Bantul Regency are currently not optimal. According to SPAB e-monev study and analysis by BNPB in 2023 stated that 11% of the 8,268 schools only in DI. Yogyakarta did it. The capacity and preparedness for schools in Bantul, especially those on the Opak Fault, to face the threat of earthquakes is absolutely necessary through reinforcement of SPAB. To ensure the schools in the Opak Fault area consistently implement Disaster Safe School (SPAB) standards in increasing preparedness to face earthquakes, periodic self-assessments should be carried out. However, self-assessment using Inarisk SPAB's (Disaster Safe School) e-monev tools in the Opak Fault has not been optimal, which means that schools have not attempted to provide guarantees of optimal preparedness to face the risk of earthquake disasters for its members. This research is qualitative research with a descriptive approach involving 32 key informan and triangulation. The results are stated that four of six schools in Opak Fault, Bantul Regency are less prepared to face earthquakes, while the others are almost ready and ready category.